Perancangan Box Penerimaan Paket Berbasis IoT - Junaidi, Feri; Jasmir; Riyadi, Willy (LPPM Universitas Dinamika Bangsa, 2024)
Online buying and selling transactions are different from buying and selling transactions directly. Payment is made with a predetermined payment system and the goods will be sent through the freight forwarder. Freight forwarding services also play a very important role in the online purchase process. Common problems include damage or loss of goods, overpriced shipping costs, and irregular delivery times. Some of the problems mentioned in the delivery of goods are none other than the recipient of the goods themselves. A problem that often occurs is when the recipient is not at home or at the address to which the goods will be delivered. As a result, the goods or packages do not reach the homeowner or the person who ordered the package. From the description of the problem above, the author wants to design a box that can receive packages even though the homeowner is not at home. The system is created so that the package owner can see the condition of the package, both from the shape and weight of the package directly through cameras and sensors, so that the package owner can ensure that the package is received and stored safely.